Integrated metabolomic and transcriptomic analysis elucidates transcriptional regulation of flavonoid biosynthesis in differentially pigmented honeysuckle (Lonicera japonica) varieties - Liao, Hailei; Wu, Fang; Xie, Jixin; He, Wenying; Zhang, Xinxue; Dai, Jinxia; Liu, Hua; Li, Ming; Wang, Lijuan (Frontiers in Plant Science, 2025)
IntroductionHoneysuckle (Lonicera japonica Thunb.) is a key medicinal plant whose bioactive flavonoids underpin its antiviral, anti-inflammatory, and antioxidant properties. However, the genetic and metabolic mechanisms controlling flavonoid accumulation and the associated flower color variation between different cultivars remain largely unexplored, limiting targeted breeding for enhanced therapeutic quality.MethodsA comparative analysis was conducted using two distinct honeysuckle varieties—'Luyu No.1' (white-yellow flowers) and 'Honghua' (red-pink flowers)—at the optimal harvest stage ('Dabai period'). An integrated transcriptomics (RNA-seq) and widely targeted metabolomics approach was employed to identify differentially expressed genes (DEGs) and differentially accumulated metabolites (DAMs) between the varieties.ResultsTranscriptomic profiling revealed 5,901 DEGs, with significant enrichment in the phenylpropanoid and flavonoid biosynthesis pathways. Key structural genes (PAL, CHS, F3H, FLS, DFR, and ANS) were markedly up-regulated in 'Honghua'. Metabolomic analysis identified 399 flavonoids, including 228 DAMs. The 'Honghua' variety exhibited a 2.32-fold higher total flavonoid content, with substantially elevated levels of anthocyanidins (87.58-fold), flavanols (7.66-fold), and chalcones (6.17-fold). Critical medicinal compounds such as quercetin-3-O-rhamnoside and luteolin-7-O-glucoside were significantly enriched in 'Honghua'. Integrated analysis highlighted the co-expression of transcription factors (MYB, bHLH, NAC) with flavonoid pathways. Crucially, the anthocyanin-modifying enzymes F3’M and 3RT were up-regulated by 22.12- and 3.03-fold, respectively, in 'Honghua', while a potential repressor, TCP15 (bHLH), was down-regulated.DiscussionThe results demonstrate that the red-pink pigmentation and superior medicinal quality of 'Honghua' are driven by a coordinated gene-metabolite network that fluxes metabolic intermediates towards anthocyanin and other flavonoid end-products. The pronounced up-regulation of F3’M and 3RT is identified as a key biochemical determinant for anthocyanin diversification and color development. This study provides the first comprehensive framework for flavonoid biosynthesis in honeysuckle, establishing a genetic basis for breeding cultivars with high flavonoid content and enhanced pharmacological value.